THE CORRELATION BETWEEN POCKET MONEY AND MATHEMATICS LEARNING OUTCOMES: A QUANTITATIVE STUDY OF SIXTH-GRADE STUDENTS - Handika Suryatama; Aditya Nugrahanta; Nurfadhilah Jati Kusuma; Leonardus Rangga Satrio Nugroho; Deny Hadi Siswanto (Jurnal Padamu Negeri, 2026)
Learning progress will only be achieved if the environment is supportive; therefore, parents are expected to act more wisely regarding providing pocket money. This study uses a quantitative approach with a survey research method employing a questionnaire to investigate the relationship between pocket money and mathematics learning outcomes among sixth-grade elementary school students at Karangtengah 2 Elementary School. A total of 17 students participated as the sample in this study. Information was collected through questionnaires and relevant documentation reviews. Data analysis was conducted using descriptive statistical techniques and inferential statistical methods. The R square test analysis yielded a result of 0.0174, indicating that the influence of pocket money on mathematics learning outcomes is 1.74%, while 98.26% is influenced by other variables not examined. Based on these findings, there is a positive, though not significant, relationship between the provision of pocket money and the level of motivation in learning mathematics among students. Additionally, the findings indicate a potential positive relationship with motivation, but the direct effect on learning outcomes is minimal and not statistically significant among sixth grade students at Karangtengah 2 Elementary School.